Changes in stress levels and determinants of stress levels in University students during the covid-19 pandemic period in Aceh - Pamaila, Sri Reski; Adamy, Aulina; Maidar, Maidar; Hidayat, Melania; Abdullah, Asnawi (Science Midwifery, 2024)
The Case of Covid-19 in Indonesia from 2020 - 2021 has not shown any changes yet. The Covid-19 pandemic has crippled all areas of activity, especially in the field of education. The learning system that was previously carried out face-to-face has suddenly changed to online, where there are obstacles that trigger the emergence of stress. This study aims to determine changes in stress levels during the PSBB (Large-Scale Social Restrictions) and PPKM (Enforcement of Restrictions on Community Activities) periods and the determinants that cause changes in stress levels in students during the Covid-19 pandemic period in Aceh. This research uses a quantitative method with a cross-sectional design. The population in this study were all students in Aceh who were studying in Aceh with a sample of 122 students who had met the inclusion criteria using the random sampling method with two data collection times. The statistical tests used were the T-test and logistic regression test using STATA 14. The results of this study show that the stress levels experienced by students are in the moderate (63.11%) and severe (34.33%) categories. Of the 13 variables studied, there are 2 variables related to stress levels during the PSBB period, namely learning motivation and college assignments, and 3 variables related to stress levels during the PPKM period, namely college assignments, learning styles, and limited quotas with a p-value <0.05.